Liquid-Phase Exfoliation of Ta2NiS5 and Its Application in Near-Infrared Mode-Locked Fiber Lasers with Evanescent Field Interactions and Passively Q-Switched Bulk Laser - Shunxiang Liu; Hongfu Huang; Jinsheng Lu; Ning Xu; Junle Qu; Qiao Wen (Nanomaterials, 2022)
We report on the application of a 1 μm solid-state passively Q-switched (PQS) laser and 1, 1.5 μm mode-locked (ML) fiber lasers based on ternary chalcogenide Ta2NiS5 saturable absorber (SA), which were successfully fabricated by liquid-phase exfoliation method (LPE). The nonlinear absorption of the Ta2NiS5-SA was characterized by 0.32 GW/cm2 and 0.25 GW/cm2 saturation intensities with 7.3% and 5.1% modulations depths at 1 μm and 1.5 μm, respectively. A PQS solid-state laser operating at 1.0 μm has been realized with the Ta2NiS5-SA. The maximum average output power, shortest pulse width, pulse energy, and pulse peak power from the PQS laser are 0.257 W, 180 ns, 1.265 μJ, and 7 W. Moreover, highly stable femtosecond laser centered at 1.5 μm, and picosecond centered at 1 μm, ML fiber lasers were obtained using the Ta2NiS5-SA. A 70 dB signal-to-noise ML laser with a pulse duration of 781 fs was observed in the telecommunication window, which is better than the duration of the previously reported lasers based on Ta2NiS5. The corresponding maximum single pulse energy and peak power are 0.977 nJ and 1251 W, respectively. The Ta2NiS5-SA fabricated by the LPE method was applied in near-infrared (NIR) ML fiber lasers (evanescent field interactions) and PQS bulk lasers. The results indicate that Ta2NiS5-SA prepared by the LPE method can be applied in a 1 μm bulk PQS laser and improved by the new combination mode (evanescent field interactions) for better output performance of the fiber laser.